2021
DOI: 10.1002/mp.14767
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the predictive value of additional peritumoral regions based on deep learning and radiomics: A multicenter study

Abstract: The present study assessed the predictive value of peritumoral regions on three tumor tasks, and further explored the influence of peritumors with different sizes. Methods: We retrospectively collected 333 samples of gastrointestinal stromal tumors from the Second Affiliated Hospital of Zhejiang University School of Medicine, and 183 samples of gastrointestinal stromal tumors from Tianjin Medical University Cancer Hospital. We also collected 211 samples of laryngeal carcinoma and 233 samples of nasopharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…For the test cohort, the sensitivity and specificity of the models built with only deep learning features were usually low, which Therefore, the proportion of radiomics features in the combined model was high, and the result was good. In most of our models, the performance of either the deep learning model or the radiomics model was insufficient, making it difficult to improve the performance of the combined model, which was consistent with the conclusions of previous research (39).…”
Section: Discussionsupporting
confidence: 90%
“…For the test cohort, the sensitivity and specificity of the models built with only deep learning features were usually low, which Therefore, the proportion of radiomics features in the combined model was high, and the result was good. In most of our models, the performance of either the deep learning model or the radiomics model was insufficient, making it difficult to improve the performance of the combined model, which was consistent with the conclusions of previous research (39).…”
Section: Discussionsupporting
confidence: 90%
“…As reported in prior literature, most 11 parameters were significantly different when different ROIs were selected in the same disease [25][26][27][28]. The diagnosis and prediction values of ROIs focusing on intratumoral and peritumoral radiomic features have been compared in several studies on various tumors such as esophageal squamous cell carcinoma, glioma, breast cancer and gastrointestinal stromal tumor [11][12][13][14]. Combinations of intratumoral and peritumoral regions were reported to achieve significantly better performance in radiomics models [11][12][13][14].…”
Section: Discussionmentioning
confidence: 84%
“…The diagnosis and prediction values of ROIs focusing on intratumoral and peritumoral radiomic features have been compared in several studies on various tumors such as esophageal squamous cell carcinoma, glioma, breast cancer and gastrointestinal stromal tumor [11][12][13][14]. Combinations of intratumoral and peritumoral regions were reported to achieve significantly better performance in radiomics models [11][12][13][14]. Sun et al [11] reported that models based on peritumor regions were better behaved than those based on intratumor regions, while those that employed combined regions behaved the best.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations